User Input and Interactions on Microsoft Research ESL Assistant - Leacock, Claudia; Gamon, Michael; Brockett, Chris (ACL/SIGPARSE, 2009)
ESL Assistant is a prototype web-based writing-assistance tool that is being developed for English Language Learners. The system focuses on types of errors that are typically made by non-native writers of American English. A freely-available prototype was deployed in June 2008. User data from this system are manually evaluated to identify writing domain and measure system accuracy. Combining the user log data with the evaluated rewrite suggestions enables us to determine how effectively English language learners are using the system, across rule types and across writing domains. We find that repeat users typically make informed choices and can distinguish correct suggestions from incorrect.